An algorithm for solving a control problem for Kolmogorov systems - HOFMAN, Alexandru (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
In this paper, a numerical algorithm is used for solving control prob- lems related to Kolmogorov systems. It is proved the convergence of the algorithm and by this it is re-obtained, by a numerical approach, the controllability of the investigated problems. Mathematics Subject Classification (2010): 34H05, 93C15. Received 20 October 2022; Accepted 04 November 2022.